In Asian americans, is having a family member diagnosed with cancer associated with fatalistic beliefs? - Carolee Polek; Thomas Hardie (Asia-Pacific Journal of Oncology Nursing, 2016)
Objective: Cancer can evoke long-held cultural beliefs which either facilitate or impede efforts to expand the health literacy of families. Among these beliefs is fatalism which holds that controlling ones′ outcome is not possible, and that ones′ outcome is predestined. Some fatalistic beliefs are broadly held within the Asian American (AA) community and may be challenged or reinforced by the experience of having a family member diagnosed with cancer. This study evaluated the relationship between having a family member diagnosed with cancer and selected demographics in AAs on fatalistic beliefs. Methods: Data from 519 AA subjects from the Centers for Disease Control and Prevention Health Information Trends Survey were used to complete a secondary analysis. Descriptive statistics characterize fatalistic beliefs. Four models using four questions assessed fatalistic beliefs as dependent variables and independent variables of having or not having a family member diagnosed with cancer, completing college or not, sex, and age were assessed using ordinal regression. Results: All of the fatalistic beliefs examined were endorsed by large portions of the subjects. When considering the role of being exposed to having a family member with cancer, it was associated with an increase in the likelihood in a belief that one is likely to get cancer, and everything can cause cancer. Being exposed to a family member diagnosed with cancer was not significantly associated with believing, there was little one could do to control their cancer risk. This belief was broadly rejected. While the belief that there are so many different recommendations about preventing cancer, it is hard to know what to do, was broadly endorsed and not associated with having a family member diagnosed with cancer. Conclusions: The major practice implications within oncology nursing suggest the importance in assessing cancer health literacy and providing corrective knowledge in families with a member diagnosed with cancer. While recognizing the need for more knowledge, cancer diagnoses may represent a significant teachable moment for family members enhancing their health knowledge and supporting behavioral change. Two beliefs were contradictory and broadly held with the AA community, thus support will be needed for further public health research.